Unarousable child with a short bowel. Issue 3 (29th October 2020) - Cortellazzo Wiel, Luisa; Conversano, Ester; Carlone, Giorgia; Di Leo, Grazia; Gortani, Giulia; Zanchi, Chiara; Barbi, Egidio
Abstract : Unarousable child with short bowel: A 4-year-old boy was admitted with progressive lethargy of a few hours' duration and no other symptoms. His medical history was relevant for short bowel syndrome (SBS), following neonatal volvulus, with residual bowel length of 23 cm and intact ileocecal valve. He had similar self-limiting episodes in the past, after weaning parenteral nutrition, especially after eating large meals. The day before, he had consumed a large amount of apples. Arterial blood gas (ABG) analysis showed metabolic acidosis with normal lactacidaemia (pH 7.09, pCO2 19 mm Hg, pO2 101 mm Hg, HCO3 5.8 mmol/L, BE −24, anion gap 29.4, chloride 116 mmol/L, L-lactate level 4 mmol/L). On admission, the child could be awakened, but he was confused with slurred speech (Glasgow Coma Scale 14), with a body temperature of 37 C°, a heart rate of 125 beats/min and a respiratory rate of 38 breaths/min. The abdomen was distended, without guarding and with normal bowel sounds. Blood glucose levels were normal, as well as white blood cell count, liver and kidney function test and C reactive protein. An abdominal ultrasound ruled out an intussusception. An abdominal X-ray was performed too (see figure 1 ). Questions: Which is the most likely diagnosis? Encephalitis D-lactic acidosis Dehydration with third space fluid collection and acidosis Hereditary fructose intolerance. How is this diagnosis confirmed? D lactic dosage Breath test for bacterial overgrowth Urine organic acid dosage Search for reductive substances in the stools. How should this patient be managed? Intravenous fluids to facilitate D-lactic excretion Restrict carbohydrates in the diet Intravenous bicarbonates Antibiotic treatment to reduce bowel bacterial overgrowth. Answers can be found on page 2 .